2020
DOI: 10.1016/j.susmat.2019.e00130
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of Lead stabilizer in electroless Nickel-Boron baths: Synthesis and characterization of coatings from bismuth stabilized bath

Abstract: Only a few compounds have been completely characterized as stabilizers in alkaline electroless nickel-boron plating and most of them have serious impact on health or the environment. In this paper, the effects of bismuth salts on the bath stability and characteristics of electroless NiB deposits obtained from an alkaline electroless nickel bath reduced by borohydride are presented. The objective of this paper is to propose a healthy and environmental friendly electroless NiB coating. The process of production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 38 publications
2
20
0
Order By: Relevance
“…This might be attributed to a variation in the surface morphology: the ENB-Pb deposit presented the typical cauliflower-like structure, which led to variations in the contact area throughout the test. At the beginning, the increase in the COF was similar to that reported by several researchers [19,[34][35][36][37]. Also, it was observed that the ENB deposit's COF stabilized sooner than one of the ENB-Pb deposits, probably due to its smooth surface morphology [17].…”
Section: Ball-on-disc Wear Testsupporting
confidence: 87%
See 1 more Smart Citation
“…This might be attributed to a variation in the surface morphology: the ENB-Pb deposit presented the typical cauliflower-like structure, which led to variations in the contact area throughout the test. At the beginning, the increase in the COF was similar to that reported by several researchers [19,[34][35][36][37]. Also, it was observed that the ENB deposit's COF stabilized sooner than one of the ENB-Pb deposits, probably due to its smooth surface morphology [17].…”
Section: Ball-on-disc Wear Testsupporting
confidence: 87%
“…On the other hand, as the legislation regarding environmental subjects is regularly strengthening, increased demand for completely removing lead and thallium from EN deposition baths has been seen in the metal deposition market. In addition, a few completely lead and thallium-free baths have been presented for electroless nickel-boron deposition [15,17,19,20]. One of them, developed by Bonin et al [17], completely removed the stabilizer agent from the bath and stabilized the bath by optimizing complexing agent concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Attempts are underway to make the electroless bath more ecofriendly by replacing toxic components with environmentally benign ones. 4 Cu incorporated in EN coating enhances its brightness/smoothness, thermal and paramagnetic stability, and anti-corrosion properties. [5][6][7][8] Cu into EN coating prompts to decrease the nodule size, and the coating appears to be smooth and lustrous compared to the conventional Ni-P coating.…”
Section: Introductionmentioning
confidence: 99%
“…Besides heat/thermo-chemical treatment or nitriding, recent studies have revealed that an inclusion of a third or fourth element to form poly-alloys enhances the properties of the coatings. 1624 The inclusion of tungsten resulted in the formation of the Ni–B–W coating, 16,17 while the inclusion of molybdenum resulted in the deposition of the Ni–B–Mo coating. 18,19 A significantly higher microhardness of Ni–B–W coatings were observed compared to the binary alloy.…”
Section: Introductionmentioning
confidence: 99%
“…Other poly-alloy coatings with high hardness and wear resistance include Ni–B–Sn 22,23 and Ni–B–Bi coating. 24 Furthermore, Ni–B–Sn or Ni–B–Bi coatings were deposited from a more eco-friendly SnCl 2 /bismuth stabilized bath instead of conventional lead-based stabilizer.…”
Section: Introductionmentioning
confidence: 99%